Mating plugs and male sperm storage in Bothrops cotiara (Serpentes, Viperidae) - Barros, Veronica A. [UNESP]; Rojas, Claudio A.; Almeida-Santos, Selma M. [UNESP] (British Herpetol Soc, 2017)
We describe two new aspects of male reproduction in the pit viper Bothrops cotiara: the formation of mating plugs and epididymal sperm storage. Based on histological analyses of specimens (four males and three females), we propose that long-term sperm storage occurs in the ductus deferens, whereas macroscopic hypertrophy indicates that the epididymis may be a short-term sperm storage site. Secretions of the sexual segment of the kidneys probably form the mating plug that males deposit in the female vagina during copulation. A mating plug without sperm was observed in the spring. Future studies should address the functions and longevity of mating plugs and the role of the epididymis in Bothrops reproduction.
Keywords: ductus deferens; ductus epididymis; neotropical region; reproduction; snakes; SSK